The Relationship between Family Support and the Anxiety Level of Elderly People Who Experience Diabetes Mellitus - Wardani, Fransisca Janu; Ardinata, Ardinata; Agustriyani, Feri; Wulandari, Rizki Yeni (An Idea Nursing Journal, 2024)
Elderly patients with diabetes mellitus can have anxiety. The impact of anxiety experienced by older people includes a decrease in physical activity and quality of life. One way the patient's anxiety is influenced by family support. Survey data at the All Mider Community Health Center showed that elderly patients with diabetes from the last 6 months, January – July 2023, were 103 people. This research aims to determine the relationship between family support and the anxiety level of elderly experienced with diabetes mellitus in the working area of the health center all Mider Bandar Lampung year 2023. This research design uses a quantitative cross-sectional approach. The population in this study were elderly patients who had diabetes mellitus, with 82 samples using—the cluster Random Sampling sampling technique. The research was conducted on 1-17 December 2023 at the All Mider Community Health Center, Bandar Lampung. The research instrument was a questionnaire sheet. The analysis test uses the gamma correlation coefficient. The research results showed that 50 respondents received family support, the majority of respondents did not experience anxiety, 30 respondents (60%), and 11 respondents (22%) experienced mild anxiety. Thirty-two respondents did not receive family support, the majority of respondents experienced severe anxiety, 21 respondents (65.6%), and 5 respondents (15.6%) experienced mild anxiety. The conclusion is that there is family support with the level of anxiety of older adults who experience diabetes mellitus with a p-value of 0.000. Therefore, it is hoped that community health centers will develop health services for the community to improve the quality of services, especially in socializing the importance of family support for diabetes mellitus patients